The Indonesian Police Reform: Police in the Reform Era based on New Institutionalism Perspective - ACHMAD NURMANDI; ISNAINI MUALLIDIN; EKO PRIYO PURNOMO; SURYANTO SURYANTO (Universitas Muhammadiyah Yogyakarta, 2016)
Since the reformation and democratization movement in 1998, Indonesians have faced a chronic corruption problem. At the beginning of reformation era in1998 to fight against corruption, the Indonesian government reforms the organization structure of the Indonesia Police to be an independent body separated from the Military organization. The police reforms begun in 1999 and got legal foundation with Act No. 2/2002. However, since fourteen years, the level of police reform has not yet succeed because of low community satisfaction on police service and the intense conflicts always occur whenever ACA investigates the case of corruptions conducted by police leaders. Three conflicts between police institution and ACA have taken placed. By using institutionalism approach, this research focus on the reform in police themselves are major actors on how reforms are organized and managed. This study is interpretative in nature gained only through social constructions such as language, consciousness, shared meanings, documents, tools, and other artefacts’. This finding revealed that this unsuccessful institutionalization process took place in a context of the main task of police for communicty service. Second, the study has demonstrated that three concepts from institutional theory as aforementioned provided vocabularies and insights to explain the phenomenon under study.